The Last Standard-Bearers of Biculturalism: A Quebec-Ontario Comparison of Cosmopolitan, National, Subnational, and Local Affiliations among Official Language Minorities - Bonin, Pierre-Olivier (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2022)
Despite the popularity of the cosmopolitan idea of “postnationality” and multicultural concepts of citizenship, biculturalism continues to have a lasting impact upon Canadian institutions and group loyalties. This article constitutes the first empirical investigation of affiliations among the two largest official minority language groups in Canada, Anglo-Quebecers and Franco-Ontarians. Concurring with previous research, the study finds that organizational engagement predicts stronger socio-territorial affiliations. Furthermore, evidence shows that, Franco-Ontarians are 1) less likely to be cosmopolitan than Anglo-Quebecers, 2) about equally likely to be attached to the Canadian national identity as Anglo-Quebecers, 3) more likely to identify with their province than Anglo-Quebecers, and 4) more likely to have a strong affiliation with their local polity than Anglo-Quebecers. Taken together, the findings suggest that cosmopolitanism might work better for majorities than minorities, and as a consequence for Anglophones than Francophones even when the former are in a minority setting.